Sustainable Development Goals (SDGs) and Challenges of Policy Reform on Asset Recovery in Indonesia - Qisa'i, Ahmad (UI Scholars Hub, 2020)
Absence of umbrella regulation on asset recovery is not the only challenge for effective enforcement of asset recovery and mutual legal assistance in Indonesia. Contradictory legislations, poor interagency coordination, weak capacity of law enforcement personnel and absence of center of excellence on asset recovery and mutual legal assistance are other contributing elements. Similarly, Indonesia’s commitment to fulfill the targets of Sustainable Development Goals (SDGs), especially goal 16.4, has not been met with concrete efforts. The government is hesitant to commit itself on national indicator for SDG 16.4. on asset recovery. This was shown during the two years of Kemitraan’s program to strengthen asset recovery and mutual legal assistance (SIGAP).This paper seeks to provide descriptive analysis on the results of SIGAP by posing a question on how does a development program on asset recovery in Indonesia supported by international donor contribute to overcome Indonesia’s legal and institutional challenges on asset recovery amidst Indonesia’s global commitment to SDGs. As evidenced, SIGAP exemplifies collaborative actions between various actors, state and none-state actors and national and international agencies, to increase the effectiveness of asset recovery and mutual legal assistance and policy reform needed for long term sustainability strategy in Indonesia. On SDGs, SIGAP’s decision to propose the adoption of existing national indicator on Long Term National Plan on Anti-Corruption is a deliberate and calculated decision to push for stronger commitment of Indonesian government in achieving the SDGs. The strategy indicated that by 2025, 96% of asset from corruption crimes is recovered.